A randomized, double-blind, placebo-controlled trial of niclosamide nanohybrid for the treatment of patients with mild to moderate COVID-19 - Kim, Jung Ho; Kym, Sungmin; Kim, Shin-Woo; Park, Dae Won; Kwon, Ki Tae; Seo, Jun-Won; Yu, Seungjin; Choi, Goeun; N, Sanoj Rejinold; Choy, Jin-Ho; Jin, Geun-woo; Choi, Jun Yong (Nature communications, 2025)
Effective and reliable treatments for SARS-CoV-2 infections are a key part of global COVID-19 management. Based on vitro studies, niclosamide has been considered as a potential drug candidate for SARS-CoV-2, but its clinical development has been limited due to poor solubility and bioavailability. Here we report results from a randomized, double-blind, placebo-controlled clinical trial involving 300 patients (Clinical Trial Registration Number: KCT0007307) that assessed the efficacy and safety of the niclosamide nanohybrid CP-COV03 at two different doses. Oral CP-COV03 was well tolerated, with no serious adverse events reported in any treatment group. The primary endpoints demonstrated that CP-COV03 significantly alleviated all 12 FDA-recommended COVID-19 symptoms, with symptom improvement sustained for more than 48 h. Additionally, CP-COV03 reduced SARS-CoV-2 viral load by 56.7% within 16 h of the initial dose compared to baseline. Secondary endpoints, including time to sustained symptom resolution, time to return to usual health, and reduction in hospitalization risk, also showed favorable results in the CP-COV03 group compared to placebo. These findings indicate that CP-COV03 is a safe and effective therapeutic option for the treatment of mild to moderate COVID-19 and represents a promising advancement in the repurposing of niclosamide through nanohybrid engineering. Niclosamide has been shown to have activity against SARS-CoV-2 in vitro, but poor bioavailability has hindered clinical development. In this clinical trial, the authors show that the niclosamide nanohybrid CP-COV03 alleviates COVID-19 symptoms and reduces viral load, offering a promising therapeutic option.